2018
DOI: 10.1371/journal.ppat.1006802
|View full text |Cite
|
Sign up to set email alerts
|

Regional and subtype-dependent miRNA signatures in sporadic Creutzfeldt-Jakob disease are accompanied by alterations in miRNA silencing machinery and biogenesis

Abstract: Increasing evidence indicates that microRNAs (miRNAs) are contributing factors to neurodegeneration. Alterations in miRNA signatures have been reported in several neurodegenerative dementias, but data in prion diseases are restricted to ex vivo and animal models. The present study identified significant miRNA expression pattern alterations in the frontal cortex and cerebellum of sporadic Creutzfeldt-Jakob disease (sCJD) patients. These changes display a highly regional and disease subtype-dependent regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 102 publications
(134 reference statements)
1
53
0
Order By: Relevance
“…Studies on miRNA alterations were conducted in the brain of patients afflicted with sporadic Creutzfeldt-Jakob disease (sCJD) ( Montag et al, 2009 ; Lukiw et al, 2011 ; Llorens et al, 2018 ), Fatal Familial Insomnia (FFI) ( Llorens et al, 2018 ) and Gerstmann–Sträussler–Scheinker syndrome (GSS) ( Lukiw et al, 2011 ).…”
Section: Mirna Signatures In the Brain Of Prion Diseases-afflicted Inmentioning
confidence: 99%
“…Studies on miRNA alterations were conducted in the brain of patients afflicted with sporadic Creutzfeldt-Jakob disease (sCJD) ( Montag et al, 2009 ; Lukiw et al, 2011 ; Llorens et al, 2018 ), Fatal Familial Insomnia (FFI) ( Llorens et al, 2018 ) and Gerstmann–Sträussler–Scheinker syndrome (GSS) ( Lukiw et al, 2011 ).…”
Section: Mirna Signatures In the Brain Of Prion Diseases-afflicted Inmentioning
confidence: 99%
“…In prion disease specifically, miR‐124‐3p has been shown to become significantly upregulated in mouse hippocampal CA1 neurons at 70 and 90 days post scrapie infection, while contrarily becoming downregulated at 130 and 160 days post infection . In human post‐mortem sCJD frontal cortical and cerebellar samples, miR‐124‐3p was similarly found to be decreased relative to control tissues . This conserved temporal regulation in miR‐124‐3p expression indicates a potential role of this miRNA in prion disease pathology.…”
Section: Discussionmentioning
confidence: 93%
“…Several miRNAs, most notably miR‐124‐3p, miR‐146a‐5p and miR‐342‐3p, have been found to become consistently deregulated following prion infection in GT1‐7 neuronal cells , RML inoculation in mice , scrapie infection in sheep , BSE infection in macaques and sporadic Creutzfeldt‐Jakob disease (sCJD) in humans . These miRNAs also display similar spatiotemporal expression patterns during prion disease pathogenesis and in sCJD subtypes , implying that mechanisms of deregulation may be conserved across species. Intriguingly, miR‐124‐3p, which is highly expressed in almost all brain regions , has also been found to be downregulated in the brains of patients suffering from Alzheimer’s and Huntington’s disease .…”
Section: Introductionmentioning
confidence: 99%
“…In CB, miRNAs 146a-5p, 154-5p, 26a-5p, 378a-3p, 449a, 142-3p, let7i-3p, and 5701 were upregulated, and miRNAs 124-3p and 877-5p were downregulated in sCJD. The rest of miRNAs, which expression was only altered in FC did not present changes in the CB ( Llorens et al, 2018 ).…”
Section: Regulation Of Mirnas In Prion Diseasesmentioning
confidence: 98%
“…Similarly, Miller et al (2013) also showed the upregulation of miRNA-16 in PD patients. Llorens et al (2018) demonstrated the miRNA signature in frontal cortex (FC) and cerebellum (CB) of sporadic CJD patients. In sCJD FC, miRNAs 29b-3p, 342-3p, 146a-5p, 154-5p, 195-5p, 26a-5p, 16-5p, 449a, 142-3p, let7i-5p, and 135a-5p were upregulated, while miRNAs 124-3p, 331-3p, 877-5p, and 125a-5p were downregulated compared to controls.…”
Section: Regulation Of Mirnas In Prion Diseasesmentioning
confidence: 99%